(untitled) (Dhaka University Journal of Linguistics, 2011)
Till recently freshmen at all the departments of the Faculty of Humanities of Dhaka University compulsorily attended a centrally conducted English language skills development course titled the English Foundation Course. Since 2006 the Foundation Course was discontinued and replaced by individual courses conducted by the respective departments. However neither the English Foundation Course nor the present individual courses were designed on the basis of Needs Analysis - the primary pre-requisite of any curriculum design nor have they ever been evaluated. This article presents the findings of a formal needs analysis and evaluation conducted by the researcher. Key Words: Needs Analysis; Evaluation; Language skills and sub-skills; Course usefulness and difficulty; Classroom teaching style DOI: 10.3329/dujl.v2i4.6900 Dhaka University Journal of Linguistics Vol.2(4) August 2009 pp.59-91